2015
DOI: 10.1007/s10336-015-1299-x
|View full text |Cite
|
Sign up to set email alerts
|

Tropical countryside riparian corridors provide critical habitat and connectivity for seed-dispersing forest birds in a fragmented landscape

Abstract: We conducted extensive mist netting and radio tracking of common frugivorous, seed-dispersing, and tropical forest-dwelling blue-crowned manakins (Lepidothrix coronata; BCMA) and white-ruffed manakins (Corapipo altera; WRMA) to study their habitat use, movements, breeding success, and seed dispersal potential in the fragmented landscape of southern Costa Rica. We obtained 1354 GPS locations from 20 BCMAs and 4040 GPS locations from 54 WRMAs we tracked. These birds were dependent on forest remnants and rarely m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 41 publications
(30 reference statements)
3
19
0
5
Order By: Relevance
“…3) positively and leads to long-term increases in some of the forest birds recorded there, indicating the importance of even modest efforts to keep and restore native trees in this agricultural countryside. These findings agree with our previous research showing the importance of forest remnants, riparian corridors, and individual trees for connecting this human-dominated landscape and for supporting some of the native forest bird diversity by providing breeding habitat, stepping stones for movement, habitat for surplus nonbreeders, and mosaics of different habitat types with varying phenologies of fruit, nectar, and insect production (12,13,44). Finally, populations of long-distance migratory species did better than those of the sedentary residents, in line with global assessments showing that migratory birds' mobility helps reduce their extinction likelihood (45).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…3) positively and leads to long-term increases in some of the forest birds recorded there, indicating the importance of even modest efforts to keep and restore native trees in this agricultural countryside. These findings agree with our previous research showing the importance of forest remnants, riparian corridors, and individual trees for connecting this human-dominated landscape and for supporting some of the native forest bird diversity by providing breeding habitat, stepping stones for movement, habitat for surplus nonbreeders, and mosaics of different habitat types with varying phenologies of fruit, nectar, and insect production (12,13,44). Finally, populations of long-distance migratory species did better than those of the sedentary residents, in line with global assessments showing that migratory birds' mobility helps reduce their extinction likelihood (45).…”
Section: Discussionsupporting
confidence: 92%
“…As most of this landscape is already agricultural, relying on the existing forest reserves is not sufficient, and agricultural areas need to be better integrated into conservation programs. The conservation value of many tropical agricultural landscapes can be augmented substantially with modest investment and limited conflict because remnant trees, riparian strips, forest fragments, and their resident avifauna supply people and domestic animals with fruits, shade, clean water, crop pollination, and other ecosystem services (38,44,(50)(51)(52)(53). Working with individual landowners to provide them with clear incentives to conserve forest remnants should be a top priority, as exemplified by Costa Rica's successful "Payment for Environmental Services" program (54).…”
Section: Discussionmentioning
confidence: 99%
“…These results support understandings gained from regional studies that have shown that in landscapes such as Coto Brus, where low-intensity agriculture is a significant part of the land-use matrix, forested riparian corridors (Şekercioḡlu et al, 2015), clusters of trees as small as 20 m wide (Mendenhall et al, 2011), as well as secondary forest patches, can all contribute to biodiversity (Mendenhall et al, 2014), and affect resilience, stability, and ecosystem services (Karp et al, 2011). …”
Section: Discussionsupporting
confidence: 82%
“…; Sekercioglu et al . ; Zahawi, Duran & Kormann ). A second possible explanation is that we, like many field and remote sensing studies, evaluated the effect of overall forest cover, rather than presence of individual species around each plot.…”
Section: Discussionmentioning
confidence: 99%